The Obama Family Tree - Marcovitz, Hal (Broomall, Pa. : Mason Crest Publishers, 2009)
Highlights the lives of Barack Obama's ancestors, including his great-great grandparents, Louisa and Jacob Dunham, his mother, Stanley Ann Dunham, his father, Hussein Onyango Obama; his wife's ancestors; and his children.
Celebration in Kenya -- Deep roots in Kansas -- African heritage -- A descendant of slaves -- Drawn to political activism -- A new generation.
Includes bibliographical references (p. 61) and index.
Keywords: Obama, Barack -- Family